Integration of distributed generation in the power system - Bollen, Math H. J., 1960- (Hoboken, N.J. : John Wiley & Sons, 2011)
'The integration of new sources of energy like wind power, solar-power, small-scale generation, or combined heat and power in the power grid is something that impacts a lot of stakeholders: network companies (both distribution and transmission), the owners and operators of the DG units, other end-users of the power grid (including normal consumers like you and me) and not in the least policy makers and regulators. There is a lot of misunderstanding about the impact of DG on the power grid, with one side (including mainly some but certainly not all, network companies) claiming that the lights will go out soon, whereas the other side (including some DG operators and large parks of the general public) claiming that there is nothing to worry about and that it's all a conspiracy of the large production companies that want to protect their own interests and keep the electricity price high. The authors are of the strong opinion that this is NOT the way one should approach such an important subject as the integration of new, more environmentally friendly, sources of energy in the power grid. With this book the authors aim to bring some clarity to the debate allowing all stakeholders together to move to a solution. This book will introduce systematic and transparent methods for quantifying the impact of DG on the power grid'--
'Gives a power-system viewpoint contrary to the energy viewpoint presented in many other books on DG Emphasis on systematic and transparent calculation methods allowing a quantification of the amount of DG that can be integrated at a certain location of the grid or in the grid as a whole Provides an overview of the different energy sources, with emphasis on windpower, solar power and CHP (Combined Heat & Power) Provides a general overview of the different methods available to allow more DG to be connected to the grid, ranging from classical methods like building more lines, to advanced methods like power-electronics control, and even future methods like smartgrids and microgrids'--
Includes bibliographical references (p. 471-495) and index.
Keywords: Distributed generation of electric power